2016
DOI: 10.17795/jhealthscope-39432
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Health Promoting Behaviors Through the Health Locus of Control in a Sample of Adolescents in Iran

Abstract: Background: Health promoting behaviors are amongst the best methods through which people can maintain and control their health. Objectives: The aim of this study was the prediction of health promoting behaviors through the health locus of control in a sample of adolescents in Bandar Abbas, in the south of Iran. Methods: In this cross-sectional study, the Wallston questionnaire and adolescent health promoting scale were used for data collection. From the 378 distributed questionnaires among the students, 342 qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…It was observed that both internal and powerful others HLOC positively predicted aspects of health-promoting behaviors. This finding was in line with those of studies conducted in Asian countries, Iran [ 24 ] and Turkey [ 25 ]. In general, the belief that one is in charge of one’s own life facilitates engagement in self-benefitting acts.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was observed that both internal and powerful others HLOC positively predicted aspects of health-promoting behaviors. This finding was in line with those of studies conducted in Asian countries, Iran [ 24 ] and Turkey [ 25 ]. In general, the belief that one is in charge of one’s own life facilitates engagement in self-benefitting acts.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, chance HLOC negatively predicted health-promoting behaviors through less active practical and more distractive coping strategies. Earlier studies have also demonstrated the negative role of chance HLOC in taking practical initiatives to improve one’s life [ 21 , 22 , 24 , 25 ]. People who believe that their situation is determined by random events are less likely to take active measures to change their lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent use of BCM, in addition to being influenced by other people, is due to the belief of chance as the main source of life control. Adolescents who used condoms in their first sexual intercourse showed greater internalization, evidencing a greater capacity for sexual negotiation with partners (9,22) . In another study, internal adolescents and with greater External locus of control (Powerful Others) had healthier dimensions of positive behaviors, which shows that health behavior is not correlated with beliefs in health being a matter of chance (23) .…”
Section: Discussionmentioning
confidence: 99%